Analysis of peel and shear strains in cracked lap shear specimens subjected to fatigue loading using digital image correlation - Alessandra Panerai; Gianmarco Piccoli; Luca Michele Martulli; Andrea Bernasconi; Michele Carboni (Acta Polytechnica CTU Proceedings, 2023)
Adhesive bonding presents many advantages, such as efficient manufacturing and improved structural performance [1]. However, in structures subjected to fatigue, cracks might initiate and propagate in joints, leading to in-service failure [2]. Most adhesively bonded joints are subjected to combination of peel and shear loads, so mixed I+II mode loading conditions are present [3]. In this work, Cracked Lap Shear specimens, which feature mixed I+II mode loading conditions, were tested under fatigue loading. During tests, crack growth was monitored using Visual Testing and Digital Image Correlation. With Digital Image Correlation, opening and sliding displacements in the bondline were extracted from the substrates’ displacement fields and compared against a Finite Element Model, revealing a highly strained process zone ahead of the crack tip. Results highlight the usefulness of DIC in capturing the deformation behaviour of adhesive joints under mixed mode loading conditions.